Enhancing the quality and shelf life of chevon using orange peel extract - Murshed, HM; Akter, M; Mukta, SP; Mubin, MRH; Parvin, S; Kabir, AKMA; Hossain, MM; Hashem, MA (Meat Research, 2023)
The experiment was conducted to find out the effect of different levels of orange peel extract as a natural antioxidant and antimicrobial agent on fresh and preserved chevon. For this purpose, fresh chevon samples were divided into four treatment groups. These were treated as T0 (control group 0% orange peel extract), T1 (0.2% orange peel extract), T2 (0.3% orange peel extract) and T3 (0.4% orange peel extract) respectively. Sensory tests (color, flavor, tenderness, juiciness and overall acceptability), proximate components (DM, CP, EE and Ash), physicochemical quality (Raw meat pH, cooking loss), biochemical properties (POV, FFA and TBARS) and microbial assessment (TVC, TCC and TYMC) examination were determined in order to evaluate the effect of orange peel extract as natural antioxidant and antimicrobial agent for maintaining chevon qualities and the shelf-life of chevon for 0, 5, 10 and 15 days of storage period under refrigeration temperature. Among the four treatments T3 (0.4% orange peel extract) was the best in terms of nutrient quality, physicochemical properties, biochemical analysis and microbial assessment. Therefore, it is concluded that 0.4% orange peel extract may be used up to 15 days for chevon preservation.